Analisisis Badan Penanggulangan Bencana Daerah Kota Surabaya Dalam Penangganan Bencana Banjir Di Kota Surabaya - Syahrul Cahya Ramadhan; Pradana (Publika, 2025)
Flood disaster management is an essential effort to ensure public safety, especially in urban areas with high disaster vulnerability. Surabaya City is one of the major cities in Indonesia that frequently experiences flooding due to geographical conditions and high rainfall. This study aims to analyze the role of the Regional Disaster Management Agency (BPBD) of Surabaya City in flood disaster management. This research uses a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman. The analytical framework uses Bruce J. Biddle’s role theory consisting of expectation, norms, performance, and evaluation. The results show that BPBD Surabaya has performed its role in flood disaster management, but the implementation is not yet optimal, especially in terms of cross-sector coordination, limited resources, and low community participation in disaster mitigation. Therefore, strengthening institutional capacity and increasing community involvement are necessary to improve the effectiveness of flood disaster management.